State aid & competition: The TAP case - Ponte, Rodrigo Alexandre Guerreiro (2022)
This thesis aims to provide an insight into the entire process of State aid. Using the recent measure of State aid approved by the European Commission to give support to the Portuguese airline company TAP, we explore how the process of State aid is conducted, what are its aims, and how it affects the market in which the firm on the receiving end of the State Aid operation is inserted, from the perspective of both firms and consumers alike. For this end, we work with flight data gathered directly from official sources such as Google Flights and the official website the airline company easyJet. Using the data collected, we assessed the Herfindahl-Hirschman Index (HHI) in order to measure the market concentration of the markets in question. Furthermore, we discuss the general aims of the applicable policies as well as their implementation and consequences. We find that the most important policies succeed in their main objectives of mitigating the distortions of market competition caused by the application of a State Aid operation.